Low-Intensity Focused Ultrasound Stimulator Using Focal Depth Controller for Improved Targeting in Neuromuscular Rehabilitation - Oh, Sungjin; Kim, Dong Hwee; Youn, Inchan (2017 39TH ANNUAL INTERNATIONAL CONFERENCE OF THE IEEE ENGINEERING IN MEDICINE AND BIOLOGY SOCIETY (EMBC), 2017)
Low-intensity ultrasound can be used for noninvasive neuromuscular stimulation to enhance the recovery of injured peripheral nerves and muscles. In order to improve the stimulation efficiency, focused ultrasound (FUS) with a high energy density should be used. Because the FUS is concentrated at a miniaturized focal area, deliberate targeting with focal depth control is required to achieve the accurate stimulation. In this study, a low-intensity focused ultrasound (LIFU) stimulator with a focal depth controller is presented as an effective ultrasound stimulation system for the neuromuscular rehabilitation. In the developed stimulator, the target depth is adjusted by the focal depth controller with the brief structure. The experimental results show that the developed stimulator can generate the high quality LIFU stimulation with the spatial average-pulse average intensity (I-SAPA) of 496 mW/cm(2), which is sufficient to improve the rehabilitation of injured peripheral nerves and muscles. In the in vivo experiment, a rat's sciatic nerve was successfully targeted by the developed stimulator. These results indicate that the developed stimulator can be used to improve the quality of the ultrasound stimulation for neuromuscular rehabilitation by targeting a specific area.